Non-isothermal crystallisation behaviour of a Cr–Fe–Ni–Co–Mo–Si amorphous coating. (March 2022) - Ma, Tao; Song, Peng; Dong, Quan; Tan, Jun; Huang, Taihong; Li, Zan; Liang, Yuwei; Zhang, Defeng
Abstract: The kinetics and mechanism of crystallisation of a Cr–Fe–Ni–Co–Mo–Si amorphous coating were studied using differential scanning calorimetry, owing to its relatively complex crystallisation behaviour. The premise of the production and application of amorphous materials is to understand the crystallization process of amorphous materials. It is closely related to the thermal stability of materials. Thermal stability is an important parameter to determine the effective working limit of materials. This study provides significant guidance for obtaining amorphous materials with excellent performance by controlling the crystallisation process and predicting the crystallisation failure of the coating in service. In the non-isothermal crystallisation process, results showed that the apparent activation energy ( E x ) corresponding to the temperature of the onset of crystallisation was greater than those corresponding to the glass transition ( E g ) and peak crystallisation ( E p ) temperatures; E x, E g, and E p were calculated using the Kissinger and Ozawa methods. This finding revealed that for the amorphous coating, the nucleation process was more difficult than overcoming the energy barrier for the rearrangement of atoms and the grain growth process of crystallisation. The relational plots between the local activation energy and crystallisation volume fraction under non-isothermal conditions illustrated that the crystallisation process of the amorphous coating was initially difficult but became easy in the succeeding stages. The kinetic fragility indices calculated by the Angell's method and DA equation were 16.75 and 16.42, respectively; the results suggested that the Cr–Fe–Ni–Co–Mo–Si amorphous coating was a 'strong material'. Furthermore, the two kinetic fragility indices indicate the good glass forming ability and thermal stability of the Cr–Fe–Ni–Co–Mo–Si amorphous coating.